Self-organizing production systems: Implications for product design - Gräßler, Iris; Hentze, Julian; Pöhler, Alexander (12th CIRP Conference on Intelligent Computation in Manufacturin Engineering, Nr. 79)
Current developments in production systems and production control will lead to a significant change of their connection to product development. A representative example of these developments is the concept of self-organizing production systems. This paper focuses on appropriate changes of the development process evoked through recent developments in production. The paper summarizes process changes and opportunities for the development process, which include the vision of self-organizing production systems, its challenges and opportunities. Consequences are estimated for established development methodologies like the V-model and aspects of Systems Engineering.

Main Feature List as core success criteria of organizing Requirements Elicitation - Gräßler, Iris; Dattner, Michael; Bothen, Martin (R&D Management Conference 2018 “R&Designing Innovation: Transformational Challenges for Organizations and Society”, Milan)

Systems Engineering Competencies in Academic Education - Gräßler, Iris; Hentze, Julian; Oleff, Christian (13th System of Systems Engineering Conference (SoSE))

Intelligent control of an assembly station by integration of a digital twin for employees into the decentralized control system - Gräßler, Iris; Pöhler, Alexander (Procedia Manufacturing - Proceedings of 4th International Conference on System-integrated Intelligence Intelligent, flexible and connected systems in products and production (SysInt), 19. - 20. Jun. 2018)

Semi-Automatized Assessment of Requirement Interrelations - Gräßler, Iris; Scholle, Philipp; Hentze, Julian; Oleff, Christian (Proceedings of the DESIGN 2018 15th International Design Conference)
Changing requirements have a broad impact on product development processes. In this paper, a novel approach towards structuring requirements is proposed. Based on a requirements list, interrelations of requirements are assessed semi-automatically by a rule basis. Here, generic interrelations funded on either physical fundamentals or working principles are recorded. By this approach, requirements structure matrices are derived semi-automatically. Combined with selecting critical requirements based on structured criterions, iterations due to changing requirements will be reduced.

Competitive Engineering in the Age of Industry 4.0 and Beyond - Gräßler, Iris (Proceedings of the 12th International Tools and Methods of Competitive Engineering)

V-Models for Interdisciplinary Systems Engineering - Gräßler, Iris; Hentze, Julian; Bruckmann, Tobias (Proceedings of the DESIGN 2018 15th International Design Conference)
Changes in products, markets and technologies influence the development process and its approaches. The V-Model of the VDI 2206 from 2004 is an important basis for the industrial application of mechatronic product development. This paper shows which changes need to be integrated into the updated V-Model and in which areas the focused topics have to be changed to be prepared for future challenges. For this purpose, existing applied models are analyzed and the need for rework is elaborated.

IT-Systeme für das Krisenmanagement - Pottebaum, Jens; Schäfer, Christina (Sicherheitskritische Mensch-Computer-Interaktion)

Supporting the Change to Digitalized Production Environments Through Learning Organization Development - Fischer, Christoph; Pöhler, Alexander (The Impact of Digitalization in the Workplace - An Educational View, Kapitel: Supporting the Change to Digitalized Production Environments Through Learning Organization Development)

Bedeutung des Komplexitätsmanagements für die Verbreitung von Leichtbau in Unternehmen zur Unterstützung einer nachhaltigen Produktentstehung - Gräßler, Iris; Yang, Xiaojun (Wissenschaft im Angesicht "Großer gesellschaftlicher Herausforderungen" - Das Beispiel der Forschung an hybriden Leichtbaumaterialien, Kapitel: 1.3)